AIDSImpact special issue – broadening the lens: recommendations from rehabilitation in chronic disease to advance healthy ageing with HIV. Issue 2 (13th May 2020) - O'Brien, Kelly K.; Brown, Darren A.; Corbett, Colin; Flanagan, Nick; Solomon, Patricia; Vera, Jaime H.; Aubry, Rachel; Harding, Richard
ABSTRACT: People living with HIV are ageing with a combination of physical, mental and social health challenges, known as disability. Although rehabilitation can address disability, the field is still emerging. Our aim was to identify similar disability experiences across complex chronic conditions and establish recommendations for future rehabilitation research and practice to advance healthy ageing with HIV. We conducted a consultation with 77 stakeholders from the United Kingdom, Canada, and Ireland with expertise in the fields of rehabilitation and HIV, cancer, cardiovascular disease, renal disease, or chronic obstructive pulmonary disease who attended a one-day symposium. We used facilitated discussions to identify how rehabilitation issues in complex chronic disease translate to people ageing with HIV, and prioritised recommendations for future practice and research. Disability issues experienced across HIV and other complex chronic diseases included: (i) frailty, (ii) uncertainty and worrying about the future ageing with complex chronic disease, (iii) mental health, (iv) pain, and (v) stigma. We highlight six recommendations for clinical practice and research to advance healthy ageing with HIV. Opportunities for cross-collaboration exist with other more established areas of chronic disease management and rehabilitation. Recommendations can be used to inform future HIV clinical practice and research in this emerging field.